2021
DOI: 10.12912/27197050/135523
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Passive Techniques on Thermal Behavior of Emergency Shelters

Abstract: Due to emergency situations, many people are living under degraded conditions as displaced persons and refugees.Unfortunately, shelters commonly used in humanitarian context do not ensure comfortable conditions for their occupants. This study investigates the impact of utilizing passive climatization techniques on the indoor thermal comfort of the occupants in refugee settlements under Jordan's climate using the Design Builder software. Several passive techniques were simulated, including orientation, floor, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
1
Order By: Relevance
“…The authors found that the comfort temperatures vary following the globe temperature’s variations and that are strongly related to the indoor temperature. Benefits of improved natural ventilation have been described in a recent study by Hamdan (Hamdan et al 2021 ). The author simulated the thermal behaviour of the UNHCR emergency tent, combining different passive strategies.…”
Section: Comparative Analysismentioning
confidence: 93%
“…The authors found that the comfort temperatures vary following the globe temperature’s variations and that are strongly related to the indoor temperature. Benefits of improved natural ventilation have been described in a recent study by Hamdan (Hamdan et al 2021 ). The author simulated the thermal behaviour of the UNHCR emergency tent, combining different passive strategies.…”
Section: Comparative Analysismentioning
confidence: 93%
“…This was determined using a psychrometric diagram to illustrate the strategies for bioclimatic design based on actual and simulated climatic data with reference to the ASHRAE 55 standard [14]. Thermal comfort is based on dry bulb temperature, clothing level (clo), metabolic activity (met), air velocity, humidity, and mean radiant temperature and can significantly be improved with the application of passive design solutions [15]. Indoors, it is assumed that the mean radiant temperature is close to dry bulb temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Como los espacios de vida temporal tienen una sola altura, una solución factible es la ventilación mecánica nocturna eliminando la ganancia de calor diurna mediante la inducción de aire fresco durante la noche (Medved, Babnik, Vidrih y Arkar, 2014), logrando ahorros energéticos de hasta un 47% en verano (Vidrih et al, 2016) . Además, la mejora en los sistemas de ventilación en un clima cálido y húmedo disminuye la temperatura máxima entre 5,7ºC y 14,1ºC en las horas centrales del día y reduce en 1,78ºC la temperatura media mensual (De Castro et al, 2021) (Xu et al, 2020) (Hamdan et al, 2021) (Guarino et al, 2016).…”
Section: Eficiencia Energéticaunclassified